Headscarves to Die for1: Freedom of Choice and a Freewill Symbol in Orhan Pamuk’s Snow - Hariyatmi, Sri (Indonesian Journal of English Language Studies (IJELS), 2020)
This article intends to unfold Orhan Pamuk’s conception or how he (re) presents women andtheir headscarves within Islamic tradition, with particular reference to his novel Snow. Snowopens with the return of Ka, a Turkish exile who has been leaving his country for 12 years toIstanbul in order to attend his mother’s funeral. He then decides to investigate a wave ofsuicide by young girls in the provincial city of Kars who object the ban of hijab in publicspaces. This study discovers that Pamuk explores the lamentation of the Muslim womenemanating out of the domain of religion and the will of the state as a stepping-stone to re(claim) the meaning of their headscarf and identity. Grounded in Mahmood theory, this studyargued that headscarf has a deeper meaning than just a symbol of religious devotion. It is aplatform of Muslim women’s individual will to exercise their chosen identity.Keywords: Muslim women, headscarf, religion, identity